Avaliação do comportamento eletroquímico de juntas soldadas de aço inoxidável supermartensítico por feixe de elétrons baixo vácuo - Aquino, José Mario de (2007)
The electrochemical evaluation of low vacuum electron beam weldments of supermartensitic stainless steel was carried out in terms of anodic polarization in potentiodynamic regime, intergranular corrosion by double loop electrochemical reactivation technique, pitting corrosion determination by cyclic voltammetry and by the measurement of the corrosion rate employing the polarization resistance method. The studied materials consisted of specimens extracted from the inner part of the weldments, by electroerosion, which resulted in representative samples of the base metal, heat affected zone and weld metal. The base material was a medium (12Cr-4,5Ni-1,5Mo) and high (12Cr-6,5Ni-2,5Mo) alloy of supermartensitic steel which was welded using matching consumables. In addition, samples of the autogenous condition were submitted to the analyses in order to compare the consumable effect on the corrosion behaviour. The electrochemical tests revealed that the corrosion resistance increased from the base to the weld metal, with the occurrence of precipitation redissolution in the heat affected zone. During the polarization measurements, a second activation peak arose mainly from the base metal samples. This phenomenon also appeared along the intergranular measurements and was due to the corrosion of distinct regions when cathodically reactivated. Furthermore, the degree of sensitization, represented by chromium depleted regions and measured according to intergranular corrosion tests, showed an indirect relation with pitting potential: as the sensitization areas increase, so the probability to nucleate a pit, and hence the lower is its potential. The polarization resistance method showed a dependence with the cathodic range in the medium alloy samples.